Key genes and targeted traditional Chinese medicine screening for acute kidney injury based upon bioinformatics - Hai-ting Ye; Ding-ping Yang; Peng-yan Li (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To gain a deeper understanding of molecular mechanisms underlying acute kidney injury （AKI）, explore traditional Chinese medicine strategies for managing AKI, employ bioinformatics to analyze key genes associated with AKI and predict potential Chinese herbal medicines with therapeutic effects. Methods The AKI gene expression microarray dataset GSE30718 were downloaded from the database of Gene Expression Omnibus （GEO） and GEO2R online tool was utilized for analysis. Simultaneously, AKI target genes were obtained from the Comparative Toxicogenomics Database （CTD） and the intersection of these datasets yielded the differential expression genes （DEGs） associated with AKI. Enrichment analysis and protein-protein interaction analysis were performed on DEGs. Cytoscape software was employed for identifying key genes. Subsequently, a medical information retrieval platform （Coremine Medical） was utilized for searching for traditional Chinese medicines corresponding to these key genes with the most frequently occurring ones identified. Then the database of BATMAN-TCM was employed for detailed analysis of molecular mechanisms involved in their therapeutic effects on AKI. Results For 206 DEGs, functional enrichment analysis confirmed their involvements in extracellular matrix regulation, immune-inflammatory responses and transcriptional regulation. FN1, Alb, COL1A1, JUN, TGFB1, FOS, PXDN, COL1A2, EGF and TIMP1 were identified as key genes for AKI. The potential traditional Chinese medicines for treating AKI included Danshen （Salvia Miltiorrhiza）, Renshen （Radix Ginseng）, Danggui （Angelica Sinensis） and Sanqi （Radix Notoginseng）. And Danshen had the highest frequency. The primary signaling pathway associated with Danshen's therapeutic effects on AKI was signaling pathway of phosphatidylinositide 3-kinase/protein kinase B （PI3K/AKT）. Conclusion This study has identified 10 key genes involved in AKI and their associated traditional Chinese medicines. Specific analysis of Danshen's molecular mechanisms in treating AKI provides new insights for clinical interventions and establishes theoretical rationales for subsequent researches.